Anticancer activity of silver nanoparticles synthesized from aqueous leaf extract of Solanum trilobatum (Purple fruit pea eggplant) on human oral cancer cells - Anuradha Ganesan; Gautham Kumar N; Prabhu Manickam Natarajan (Journal of HerbMed Pharmacology)
Introduction: This research explores the capability of silver nanoparticles (AgNPs) produced via friendly methods by using Solanum trilobatum leaf extract. The choice of S. trilobatum was supported by its diverse phytochemical makeup, which comprises recognized bioactive elements known for their anti-inflammatory and anti-cancer attributes. This research explores the effect of AgNPs derived from this plant as a promising eco-friendly strategy in oral cancer treatment. Methods: The synthesis of AgNPs involved employing S. trilobatum leaf extract, with observable color changes and spectral analyses confirming the unique characteristics of the nanoparticles. Fourier transform infrared spectroscopy detected distinct functional groups, whereas scanning electron microscopy (SEM) confirmed the presence of biocapped nanoparticles exhibiting various shapes and sizes spanning from 100 to 300 nm. Results: Cytotoxicity assessments via the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay revealed a half-minimal inhibitory concentration (IC50) value of 3.715 ± 0.242 μg/mL against the oral cancer (KB) cell line, indicating a significant inhibition. Acridine orange/ethidium bromide (AO/EtBr) and reactive oxygen species (ROS) assays further supported the AgNPs’ anti-cancer potential, affirming their promise for oral cancer therapy. Conclusion: AgNPs synthesized from S. trilobatum leaf extract showed substantial potential as a therapeutic agent for oral cancer. This research adds to the increasing evidence endorsing the use of environmentally friendly synthesized nanoparticles in medical treatments.